2018
DOI: 10.1080/15548627.2017.1409405
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ANXA2 (annexin A2) as a specific bleomycin target to induce pulmonary fibrosis by impeding TFEB-mediated autophagic flux

Abstract: Bleomycin is a clinically potent anticancer drug used for the treatment of germ-cell tumors, lymphomas and squamous-cell carcinomas. Unfortunately, the therapeutic efficacy of bleomycin is severely hampered by the development of pulmonary fibrosis. However, the mechanisms underlying bleomycin-induced pulmonary fibrosis, particularly the molecular target of bleomycin, remains unknown. Here, using a chemical proteomics approach, we identify ANXA2 (annexin A2) as a direct binding target of bleomycin. The interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 57 publications
(81 reference statements)
1
63
0
1
Order By: Relevance
“…Currently, BLM‐induced pulmonary fibrosis is the most classic model for exploring the pathogenesis of IPF and testing the effectiveness of new antifibrotic drugs . Recent studies have shown the mechanism of bleomycin‐induced pulmonary fibrosis: ANXA2(membrane‐associated protein A2) is a specific bleomycin target, and bleomycin binding with ANXA2 blocks TFEB (transcription factor EB)induced autophagic flux and further promotes apoptosis of epithelial cells, leading to pulmonary fibrosis . In short, BLM‐induced fibrosis animal model mimics the clinicopathological features of IPF, which is an effective model to test the effects of novel pharmacological agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, BLM‐induced pulmonary fibrosis is the most classic model for exploring the pathogenesis of IPF and testing the effectiveness of new antifibrotic drugs . Recent studies have shown the mechanism of bleomycin‐induced pulmonary fibrosis: ANXA2(membrane‐associated protein A2) is a specific bleomycin target, and bleomycin binding with ANXA2 blocks TFEB (transcription factor EB)induced autophagic flux and further promotes apoptosis of epithelial cells, leading to pulmonary fibrosis . In short, BLM‐induced fibrosis animal model mimics the clinicopathological features of IPF, which is an effective model to test the effects of novel pharmacological agents.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Recent studies have shown the mechanism of bleomycin-induced pulmonary fibrosis: ANXA2(membrane-associated protein A2) is a specific bleomycin target, and bleomycin binding with ANXA2 blocks TFEB (transcription factor EB)induced autophagic flux and further promotes apoptosis of epithelial cells, leading to pulmonary fibrosis. [19] In short, BLM-induced fibrosis animal model mimics the clinicopathological features of IPF, which is an effective model to test the effects of novel pharmacological agents. In this study, we established two models: bleomycin-induced inflammatory model and pulmonary fibrosis model to evaluate the antifibrotic effects of anlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…Insu cient autophagy might result in the senescence of pulmonary epithelial cells and the activation of myo broblasts in pulmonary brosis [15], and autophagy was inhibited in IPF patients [16]. In lung epithelial cells, bleomycin could induce pulmonary brosis in mice by impeding TFEB-mediated autophagic ux [17]. The AMPK-dependent activation of autophagy enhances collagen turnover to deactivate myo broblasts, which attenuates BLM-induced pulmonary brosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise molecular mechanisms of IPF remain to be fully revealed, and thus the optimal therapeutic treatment has not yet been developed [6][7][8][9]. In previous study, we found that ANXA2 was a special target of bleomycin and contributed to the development of pulmonary fibrosis by blocking TFEB-induced autophagy [30]. ANXA2 is required for multiple biological functions such as signal transduction, inflammation, EMT, oxidative balance, angiogenesis, cell proliferation and apoptosis, airway epithelial wound repair etc., all of which are also believed to be important pathologic mechanisms of pulmonary fibrosis [20,21,37,[48][49][50][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…In previous study, we found that ANXA2-bleomycin binding inhibited TFEB-induced autophagy flux, which contributed to bleomycin-induced pulmonary fibrosis [30]. The pathologic mechanisms of pulmonary fibrosis is complex, in addition to autophagy, chronic inflammation and cytokines production were widely accepted to play a role in pulmonary fibrosis [5,[36][37][38][39].…”
Section: The Expression Of Anxa2 Was Not Altered In Bleomycin-triggermentioning
confidence: 93%